Measurement of the [Formula: see text] production cross section using events in the [Formula: see text] final state in pp collisions at [Formula: see text] - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Flechl, M; Friedl, M; et al. (The European physical journal. C, Particles and fields, 2017)
The cross section of top quark-antiquark pair production in proton-proton collisions at [Formula: see text] is measured by the CMS experiment at the LHC, using data corresponding to an integrated luminosity of 2.2[Formula: see text]. The measurement is performed by analyzing events in which the final state includes one electron, one muon, and two or more jets, at least one of which is identified as originating from hadronization of a b quark. The measured cross section is [Formula: see text], in agreement with the expectation from the standard model.